Analysis of Resonance Characteristics of the Marine Six Branch Coaxial Herringbone Gear Transmission System - Wang Chunling; Liu Linlin; Wang Sanmin; Zhao Yongjin; Wang Ji; Wang Yongfan (Jixie chuandong)
The application of the multi-branch gear transmission in the power transmission system of high-power ships is increasing gradually. The elastic shaft structure used to realize the uniform load of each branch will lead to the reduction of the natural frequency of the transmission system, which will increase the possibility of resonance during operation. Based on the commercial finite element software (Ansys), a finite element model of a marine six-branch coaxial herringbone gear transmission system is established. The rotational degrees of freedom are reserved at each support, and the remaining degrees of freedom are constrained. The first 20 orders of natural frequencies and vibrations of the transmission system are calculated. Based on the Campbell diagram, the resonance characteristics of the system are analyzed for cruise speed. The influence law of the elastic shaft stiffness on the natural frequency of the system is studied, and the value range of the elastic shaft stiffness to avoid the resonance of the transmission system is obtained, which provide some reference for the vibration reduction design of the six-branch coaxial herring gear transmission system.